A Review on the Modeling of the Clinching Process Chain - Part I: Design Phase - Schramm, Britta; Martin, Sven; Steinfelder, Christian; Bielak, Christian Roman; Brosius, Alexander; Meschut, Gerson; Tröster, Thomas; Wallmersperger, Thomas; Mergheim, Julia (Journal of Advanced Joining Processes)
Keywords: Mechanical Engineering; Mechanics of Materials; Engineering (miscellaneous); Chemical Engineering (miscellaneous)

Numerical and experimental investigation of the transmission moment of clinching points - Steinfelder, C.; Kalich, J.; Brosius, A.; Füssel, U. (IOP Conference Series: Materials Science and Engineering)
In clinching, the combinations of requirements, materials, component dimensions and tools influence the resulting joint geometry and the resulting bonding mechanisms. These in turn affect the property profile of the joint. For example, it is possible to use different tools to flexibly adapt clinching points to the respective required load regime. Clinching points dimensioned in this way can be geometrically similar, but have different mechanical stress states, which leads to different properties in terms of load-bearing behavior. Within the scope of this work, the clinching process with different tools in optimal and compromise design and its effect on the force and form-closure component, is investigated in a torsion test of the clinched connection. Clinched steel sheets with two thicknesses and joining directions are analyzed. Virtual experiments are carried out using finite element analyses (FEA) of the joining process and are followed by a springback simulation. Subsequently, the surface pressure between the two joining partners in the clinching points is calculated on the basis of the results from the FEA and the transmittable moment of the connection, as an indicator for the force-closure component, is determined. Finally, the experimental and simulated data are compared and discussed.

Joining with Friction Spun Joint Connectors – Manufacturing and Analysis - Wischer, Christian; Steinfelder, Christian; Homberg, Werner; Brosius, Alexander (IOP Conference Series: Materials Science and Engineering)
Nowadays, the production of modern lightweight structures, like a body in white structure requires a wide variety of mechanical joining processes. To fulfill the various demands, mechanical joining processes and joining elements (JE) are used. Very often, they are adapted to the application, which leads in turn to a numerous of different variants, high costs, and loss of the process chain versatility. To overcome this drawback, an innovative approach is the usage of individually produced and task-adapted JE, the so-called friction spun joint connectors (FSJC). These connectors can be modified in shape as well as in material properties. This flexibility offers high potential for lightweight design but also increases the necessary analytical effort regarding the forming process as well as the manufactured joint's properties. Therefore, a new analysis strategy based on the Finite-Element-Method (FEM) is proposed, which numerically determines the local load bearing capacity within a given joint in order to identify the critical regions for load transfer. The process of joining element manufacturing and the analysis strategy will be described in detail and optimization results of the joints are shown. Numerical results are discussed and possible recommendations for joint manufacturing are derived.

A First Approach for the Treatment of Galvanic Corrosion and of Load-Bearing Capacity of Clinched Joints - Harzheim, S.; Steinfelder, C.; Wallmersperger, T.; Brosius, A. (Key Engineering Materials)
Corrosion is a major cause for the failure of metallic components in various branches of the industry. Depending on the corrosion severity, the time until failure of the component varies. On the contrary, a study has shown that certain riveted metal joints, exposed to a short period of mechanical loading and corrosion, have greater fatigue limits. This study gives rise to the question how different corrosion exposure times affect joint metallic components. In the present research, a theoretical approach is developed in order to evaluate the influence of galvanic corrosion on joint integrity of clinched metal joints. At first, the framework for modeling galvanic corrosion is introduced. Furthermore, a simulative investigation of a clinching point is carried out based on the assumption that corrosion leads to a reduction of the contact area which leads to a local increase in contact pressure. For this purpose, the stiffness values of individual elements in a finite element model are reduced locally in the contact area of the undercut and the contact stress along a path is evaluated. Summarizing, a modeling approach is introduced to investigate corrosion effects on load-bearing behavior of clinched joints.

Load Path Transmission in Joining Elements - Steinfelder, Christian; Martin, Sven; Brosius, Alexander; Tröster, Thomas (Key Engineering Materials)
The mechanical properties of joined structures are determined considerably by the chosen joining technology. With the aim of providing a method that enables a faster and more profound decision-making in the spatial distribution of joining points during product development, a new method for the load path analysis of joining points is presented. For an exemplary car body, the load type in the joining elements, i.e. pure tensile, shear and combined tensile-shear loads, is determined using finite element analysis (FEA). Based on the evaluated loads, the resulting load paths in selected joining points are analyzed using a 2D FE-model of a clinching point. State of the art methods for load path analysis are dependent on the selected coordinate system or the existing stress state. Thus, a general statement about the load transmission path is not possible at this time. Here, a novel method for the analysis of load paths is used, which is independent of the alignment of the analyzed geometry. The basic assumption of the new load path analysis method was confirmed by using a simple specimen with a square hole in different orientations. The results presented here show a possibility to display the load transmission path invariantly. In further steps, the method will be extended for 3D analysis and the investigation of more complex assemblies. The primary goal of this methodical approach is an even load distribution over the joining elements and the component. This will provide a basis for future design approaches aimed at reducing the number of joining elements in joined structures.

Joint point loadings in car bodies – the influence of manufacturing tolerances and scatter in material properties - Martin, Sven; Tröster, Thomas (ESAFORM 2021)

Identification of joints for a load-adapted shape in a body in white using steady state vehicle simulations - Martin, Sven; Schütte, Jan; Bäumler, C.; Sextro, Walter; Tröster, Thomas (Forces in Mechanics)

A New Approach for the Evaluation of Component and Joint Loads Based on Load Path Analysis - Steinfelder, C.; Brosius, A. (Lecture Notes in Production Engineering)

Probability Distribution of Joint Point Loadings in Car Body Structures under Global Bending and Torsion - Martin, Sven; Camberg, Alan A.; Tröster, Thomas (Procedia Manufacturing)